Al-Sisi's development visions: Projects and power in Egypt - Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2014)
Abdul Fatah al-Sisi came out as winner of a highly unfree and unfair presidential election held between 26 and 28 May. In office the former military chief now faces great challenges. The country's economy is in ruins and living conditions have tumbled over the past three and a half years. But comprehensive economic reforms are not on al-Sisi's agenda. Instead, during his election campaign, the former army chief proposed gigantic development projects. Here he has a particularly firm eye on the interests of his most important supporters. Such a course will not improve Egypt's economic and social situation. Germany and Europe should therefore definitely not support the approach of the new leadership in Cairo, but instead push for structural reforms in the Egyptian economy. (SWP Comments)
Keywords: 320